Differentiated Learning : The Implementation of Student Sensory Learning Styles in Creating Differentiated Content - Erna Sulistianingrum; Endang Fauziati; Wafrotur Rohmah; Ahmad Muhibbin (Jurnal Paedagogy, 2023)
This research aims to explore the implementation of students' sensory learning styles in creating differentiated content and the factors that contribute to it. The research method used was a case study with a qualitative approach. The data sources in this study were five science teachers in Grobogan District and the content documents/teaching materials they made. Interviews, questionnaires, and documentation were used to collect the data observation. In-depth observations were made in four state junior high schools. There were state junior high school 1 Purwodadi, state junior high school 1 Wirosari, state junior high school 1 Tegowanu, and state junior high school 1 Klambu. Five science subject teachers were interviewed to obtain data on implementing students' sensory learning styles in creating differentiated content and the factors that contribute to it. Questionnaires were given and filled out by the mover teachers after the interview. Documentation of content created by mover teachers was also carried out to obtain accurate data. Data validity used triangulation of sources and techniques. The results of the study showed that: (1) Students' sensory learning styles were implemented in the creation of differentiated content; (2) several factors contribute to the implementation of students' sensory learning styles in creating differentiated content, including internal factors and external factors. Internal factors include the teacher's educational background and teaching practices in class. The external factors consisted of facilities and infrastructure, and time.